ANALISIS KASUS PENDING KLAIM SEBAGAI DASAR PERANCANGAN APLIKASI AUDIT KODING INTERNAL DI RUMAH SAKIT - Yastori; Nurul Fitri Khumaira (LPPM Universitas Awal Bros, 2025)
Pending claims in hospitals impact cash flow constraints, increase verifier workloads, and disrupt operational stability and service quality. This study aims to analyze pending claims cases as a basis for designing a claims audit application in hospitals. The type of research used in this study is descriptive quantitative research, namely research that uses numbers to describe, explain, and draw conclusions from a phenomenon. Research with quantitative methods uses research data in the form of numbers for statistical processing of frequency distributions, calculating data percentages and analyzing pending claims cases based on BPJS regulations and ICD-10 and ICD-9-CM coding rules. The population of the study was 616 cases. The sample in this study was 15 pending claims cases determined by the Purposive Sampling technique. The results of this study obtained the main problems of pending claims at Hospital X include coding errors, incomplete mandatory supporting documents (examination results, PA, microbiology), and differences in perception with BPJS, can be minimized through strategic solutions in the form of increasing accuracy in reviewing medical record documents and claims to ensure completeness, compliance with regulations (BA, PMK, ICD), and building a strong perception of equality between DPJP and all verifiers. Further research is recommended for the design of prototypes and web-based applications that are fully functional, so that they can be used in real life in the internal claim audit process to minimize pending claims in hospitals.